KOMODIFIKASI DALAM ASPEK PRODUKSI PESAN PERGELARAN WAYANG KULIT PURWA GAYA SURAKARTA ANALISIS WACANA KRITIS PAKELIRAN GARAP SEMALAM LAKON âMAKUTHARAMAâ SAJIAN KI PURBO ASMORO - , RUDY WIRATAMA; , Drs. Widodo Agus Setianto, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wayang kulit purwa is a kind of performing arts which has deeply rooted in the life of Javanese society. As a mean of traditional communication media, wayang show has two sides which appeared in community: the spiritual side which deals with morality and ethics, and also the profane one which contains more entertainment. Along with the rapid dynamics of society, the immediately changed values and norms demanded wayang kulit show to adapt itself with the contemporary condition. One of a solution to reach the conformity between the two is message commodification. Commodification in wayang performances was done by a dalang as a main message producer, who has responsibilities in regulating the messages in wayangâs symbolic universe which has changed into a cultural commodification, and also maintained his former role as a communicator who transmits the spiritual values in the performance. The logical consequence of commodifications i.e. the decision of compromizing, maintaining or changing values which occured inside the puppet performance, including the performance of Makutharama by Ki Purbo Asmoro, which audiovisual record used by LONTAR Foundation in 2013 as a material for Wayang Educational Package. In this research, we will talk about how the dalang as message producer acts facing the commodification, or even become the part of the commodification itself, as an effort to keep the performance successful to the audience.